Long-term re-intervention after USgHIFU and prediction of NPVR in different ages of patients with uterine fibroids - Shuang Li; Wang-wa Ma; Mei-Jie Yang; Yong-Bin Deng; Liang Hu; Jin-Yun Chen (International Journal of Hyperthermia)
Objective Long-term re-intervention after ultrasound-guided high intensity focused ultrasound (USgHIFU) ablation was reported, and the prediction of non-perfusion volume ratio (NPVR) in differently aged patients with uterine fibroids (UFs) was explored.Materials and Methods Patients with UFs who underwent USgHIFU ablation from January 2012 to December 2019 were enrolled and divided into < 40-year-old and ≥ 40-year-old groups. Cox regression was used to analyze the influencing factors of re-intervention rate, and receiver operating characteristic (ROC) curve was used to analyze the correlation between NPVR and re-intervention rate.Results A total of 2141 patients were enrolled, and 1558 patients were successfully followed up. The 10-year cumulative re-intervention rate was 21.9%, and the < 40-year-old group had a significantly higher rate than the ≥ 40-year-old group (30.8% vs. 19.1%, p < 0.001). NPVR was an independent risk factor in both two groups. When the NPVR reached 80.5% in the < 40-year-old group and 75.5% in the ≥ 40-year-old group, the risk of long-term re-intervention was satisfactory.Conclusion The long-term outcome of USgHIFU is promising. The re-intervention rate is related to NPVR in differently aged patients. Young patients need a high NPVR to reduce re-intervention risk.